Electron transfer and coupling in graphene–tungsten disulfide van der Waals heterostructures - He, Jiaqi; Kumar, Nardeep; Bellus, Matthew Z.; Chiu, Hsin-Ying; He, Dawei; Wang, Yongsheng; Zhao, Hui (Nature communications, 2014)
The newly discovered two-dimensional materials can be used to form atomically thin and sharp van der Waals heterostructures with nearly perfect interface qualities, which can transform the science and technology of semiconductor heterostructures. Owing to the weak van der Waals interlayer coupling, the electronic states of participating materials remain largely unchanged. Hence, emergent properties of these structures rely on two key elements: electron transfer across the interface and interlayer coupling. Here we show, using graphene–tungsten disulfide heterostructures as an example, evidence of ultrafast and highly efficient interlayer electron transfer and strong interlayer coupling and control. We find that photocarriers injected in tungsten disulfide transfer to graphene in 1 ps and with near-unity efficiency. We also demonstrate that optical properties of tungsten disulfide can be effectively tuned by carriers in graphene. These findings illustrate basic processes required for using van der Waals heterostructures in electronics and photonics. Two-dimensional materials get their unusual properties because the motion of their electrons is confined to a single plane, but combining two such materials adds an extra degree of freedom: interlayer coupling. Here, the authors use ultrafast spectroscopy to show that this electron motion is highly efficient.